“Work over university?” A qualitative exploration of demotivation toward higher education among Kazakhstani youth - Ashimkhanova, Symbat; Sarwar, Abdullah; Kalykov, Abay; Kaur, Dalwinder (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the factors underlying students’ demotivation to enrol in higher education, framed within management science perspectives. Guided by Human Capital Theory, Self-Determination Theory, and Expectancy Theory, we conducted qualitative interviews with 20 youths in Almaty, Karaganda, and Astana who either decided against university or left university early to work. The findings reveal a combination of empirical, contextual, and practical gaps in existing literature, as prior research has scarcely addressed Kazakhstani youth in this regard. Our results link youth decisions to forego university with perceived low returns to education and strong pull factors from the labor market, echoing global post-pandemic shifts. By integrating motivation theories, the discussion offers insights into how economic expectations, intrinsic motivation, and outcome valuations shape educational choices. Hence, this study contributes to management and education literature by illuminating why many young Kazakhstani students choose work over university, and suggests strategies for re-engaging youth in higher education. Policy implications include enhancing the perceived value of higher education, providing financial and academic support, and aligning university programs with labor market needs.